Atrioventricular Nodal Reentrant Tachycardia in Kartagener’s Syndrome - Luize, Christian Moreno; Oliveira, Lucas Hollanda; Carvalho, Ricardo Sobral de; Carvalho, Marcel Fernando Silva; Lago, Danusa Moreira; Dietrich, Cristiano de Oliveira; Nogueira, Alleh; Cirenza, Claudio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Single case report of a middle-aged patient with Kartagener’s syndrome who experienced recurrent paroxysmal supraventricular tachycardia. Despite optimized beta-blocker therapy, only cardioversion in emergency departments provided symptomatic relief. The unique electrocardiographic features of this condition and their significance in transaortic electrophysiological studies for diagnosis and treatment are highlighted.